2015
DOI: 10.1016/j.envres.2015.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprint analysis of brominated flame retardants and Dechloranes in North Sea sediments

Abstract: 53 brominated and chlorinated flame retardants were investigated in sediment samples from the German rivers Elbe and Weser, the German Bight, Jadebusen, East Frisian Coast as well as the UK East coast. The aim of the presented study was to investigate the prevalence of different halogenated flame retardant groups as contaminants in North Sea sediments, identify determining factors for the distribution and levels as well as to identify area specific fingerprints that could help identify sources. In order to do … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 25 publications
0
12
0
2
Order By: Relevance
“…However, that the concentration of Br as brominated flame retardants in marine sediment and shellfish is generally a few tens of ng g -1 or lower (Munschy et al, 2015;Suhring et al, 2015) suggests a quantity of equivalent Br in microplastic that is orders of magnitude greater.…”
Section: Implications For Plastic-consuming Seabirdsmentioning
confidence: 99%
“…However, that the concentration of Br as brominated flame retardants in marine sediment and shellfish is generally a few tens of ng g -1 or lower (Munschy et al, 2015;Suhring et al, 2015) suggests a quantity of equivalent Br in microplastic that is orders of magnitude greater.…”
Section: Implications For Plastic-consuming Seabirdsmentioning
confidence: 99%
“…However, these structural diverse compounds have the disadvantage of persistent and bioaccumulative potential, which is an issue of concern for human, animal and the environment [85]. Furthermore, so-called additive BFRs, which are implemented in the polymer material, may migrate in the environment and due to the global distribution high levels of BFRs were identified worldwide [87,88]. Therefore, the occurrence and fate of brominated flame retardants in humans and in the environment are topics of increasing concern.…”
Section: Transformation Processes Of Selected Compound Classesmentioning
confidence: 99%
“…The paper also suggests that HBCDD from the UK is being moved by ocean currents to the East Frisian Coast. 23 Another study conducted in the UK found varying HBCDD concentrations in Thames river sediment that spiked at very specific points along the industrial areas on the river, with elevated levels of the γ-isomer, indicating the presence of recent pollution sources. This illustrates that despite the European and International restrictions on HBCDD, it continues to be a problem in our environment.…”
Section: Introductionmentioning
confidence: 99%
“…21 Similar results were also recorded in the Weihe River Basin, showing a link between industrialised areas, point source pollution and HBCDD concentrations 22 with other studies also confirming that soil and sediment was the primary sink with the γ-HBCDD being the primary isomer in that environmental compartment. 3 In Europe, Sühring et al 23 measured HBCDD in surface sediment samples from the German rivers Elbe and Weser, the German Bight, Jadebusen, East Frisian Coast as well as the UK Southeast coast. Sediment samples from the river Weser and East Frisian Coast show that HBCDD was not only present, but also reflect the isomer fingerprint of the commercial mixture, with up to 90% of HBCDD in the γ-isomer form.…”
Section: Introductionmentioning
confidence: 99%